2011
DOI: 10.1002/jcb.23292
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin ligase CHIP induces TRAF2 proteasomal degradation and NF-κB inactivation to regulate breast cancer cell invasion

Abstract: Transcriptional factor nuclear factor-kappaB (NF-κB) plays a crucial role in human breast cancer cell invasion and metastasis. The carboxyl terminus of Hsc70-interacting protein (CHIP) is a U-box-type ubiquitin ligase that induces ubiquitination and proteasomal degradation of its substrate proteins. In this study, we investigated the role of CHIP in the NF-κB pathway in the invasion of MDA-MB-231 cells, a highly aggressive breast cancer cell line. We showed that overexpression of CHIP significantly inhibits th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 27 publications
3
55
2
Order By: Relevance
“…CHIP knockdown in breast cancer cells substantially elevates levels of cell invasion (47). Similarly, we observed that SKOV3 cells with CHIP knockdown exhibited increased cell invasion.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…CHIP knockdown in breast cancer cells substantially elevates levels of cell invasion (47). Similarly, we observed that SKOV3 cells with CHIP knockdown exhibited increased cell invasion.…”
Section: Discussionsupporting
confidence: 71%
“…Similarly, we observed that SKOV3 cells with CHIP knockdown exhibited increased cell invasion. The mechanism of CHIP-dependent regulation of invasion is not well understood; however, it is possible that the loss of CHIP causes the accumulation of signaling proteins such as MLK3, TRAF2, Raf-1, and ErbB2, which are key regulators of invasion (47)(48)(49). The accumulation of TRAF2 in CHIP knockdown cells might also increase cell invasion by enhancing MLK3 activation (5,17).…”
Section: Discussionmentioning
confidence: 99%
“…Signaling through TRAF2, but not TRAF1 or TRAF3, is known to promote NF-B activity, and TRAF2 is also responsible for promoting JNK/SAPK activity, inflammation, cell migration, and chemo-and radioresistance of cancer cells (41)(42)(43)(44)(45)(46)(47). Moreover, specific depletion of TRAF2 in GB has been shown to inhibit growth and confer radiosensitization to tumor cells (48).…”
Section: Discussionmentioning
confidence: 99%
“…C terminus of Hsp70-interacting protein (CHIP) is a U-box-dependent E3 ubiquitin ligase which is highly expressed in human striated muscle, aortic smooth muscle cells (SMCs), and endothelial cell [12]. Increasing evidence suggests that CHIP plays a critical role in the regulation of cell growth, apoptosis, neurodegeneration, invasion, SMC differentiation and cardiac fibrosis [13,14,15]. Recently, it is reported that CHIP also participates in innate immunity through TLR4 and TLR9, rather than TLR3-driven pathway.…”
Section: Introductionmentioning
confidence: 99%